Norma Dan Nilai Adat Istiadat Dalam Kehidupan Sehari-Hari Di Masyarakat - Iin Turyani; Erni Suharini; Hamdan Tri Atmaja (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This article examines the role of customary norms and values ​​in everyday life in society. Customary norms and values ​​are an integral part of culture that shape the identity and character of a community. The research results show that customary norms and values ​​function as behavioral guidelines, maintain social harmony, and strengthen solidarity between community members. Apart from that, customs also play a role in ritual ceremonies and various social activities that reflect togetherness and mutual cooperation. Although modernization and globalization pose challenges to the preservation of traditional customs, many communities are trying to maintain and adapt these values ​​in the contemporary context. This article emphasizes the importance of understanding and respecting traditional norms and values ​​to maintain the sustainability of local culture amidst the changing times.